Adaptability to Stress in Student Youth at Different Stages of the Russian-Ukrainian Military Conflict - Hrabovska , Sofiia; Partyko , Tetyana; Stelmashchuk , Khrystyna (Insight: the psychological dimensions of society, 2024)
The aim of the study is to identify the peculiarities of resilience in master’s students in the conditions of military conflict and to determine the influence of adaptive capacity on psychological well-being. Methods. The research uses the methodology of adaptability to stress by V. Rozov (2005) and psychological well-being by C. Riff. The mathematical and statistical data processing methods are the following: Cronbach’s (α), Scheffe Test, Pearson’s coefficient (R), rotation of factors by the Varimax normalized, standardized regression coefficient. Results. It was identified that individual qualities responsible for students’ adaptation to stress are grouped in different structures at different stages of the war. The role of individual components in the structure of adaptive capacity to stress is changing. The most important integrator of adaptive resources at all stages of war is the somatic regulation ability. At the stage of hybrid warfare, it is the adaptability of thinking, at the beginning of the full-scale invasion, it is optimism, one year after the beginning of full-scale hostilities – management of one’s psychophysiological state. At all stages of the war, an important factor in the psychological well-being of master’s students was the social support they received from their community. At the beginning of the full-scale war, somatic regulation also plays a significant role, and a year later – the ability to determine one’s life priorities. There was no influence of optimism and the ability to manage sleep on the psychological well-being of master’s students, but it was found that there is a close relationship between optimism and psychological well-being. Discussion and conclusions. It was empirically substantiated that the content of the structure of adaptive capacity to stress in master’s students is different at different stages of the war. At all stages, the adaptive core was somatic regulation, which was combined with adaptive thinking during a hybrid war, with optimism at the beginning of the full-scale war, and with the management of psychophysiological states a year later. It was proved that at different stages of the war, the psychological well-being of master’s students depended on the social support, which was combined with the positive influence of adaptive thinking, self-confidence, time management and a negative impact of somatic regulation and management of one’s own psychophysiological states during the hybrid war; in the first months of the full-scale war, it was combined with a positive influence of time management, somatic regulation and a negative impact of adaptive thinking; a year later it was combined with a positive influence of time management, self-confidence, a negative impact of management of psychophysiological states and a contradictory effect of somatic regulation.